The Northwest Passage in the Arctic: A brief assessment of the relevant marine transportation system and current availability of search and rescue services - Rebecca Sheehan; Dimitrios Dalaklis; Anastasia Christodoulou; Megan Drewniak; Peter Raneri; Angelos Dalaklis (Logistics, 2021)
The analysis in hand provides a brief assessment of the United States' and Canada's marine transportation system and relevant search and rescue (SAR) support in relation to the Northwest Passage, with the purpose of examining to what extent these countries' relevant infrastructure resources are able to meet the expected growth of shipping operations and business activities in the Arctic. Through an extensive literature review, this assessment will specifically describe the most important influences upon the maritime transportation system, with the issue of certain geographical details and the capabilities of existing ports standing out. Additionally, vessel activity trends and vessel traffic routing measure initiatives will be examined. Furthermore, the SAR infrastructure details and means to render assistance to people in distress along the Northwest Passage will be discussed. The reality remains that port characteristics are limited and vessel traffic routing measure initiatives and upgrades to SAR assets are commendable but slow-paced. It is true that both the United States and Canada are taking proper measures to build up infrastructure needs, but they both may run out of time to put adequate infrastructure in place to deal effectively with the changing environment.
Keywords: 650; Arctic shipping; infrastructure; logistics; marine transportation system; search and rescue (SAR)